(untitled) (JOURNAL OF ADVANCES IN CHEMISTRY, 2020)
Pollution is affecting river Rwabakazi in the Nile basin. Its effects are reflected by high turbidity, pH, total suspended solids, (T.S.S.), electrical conductivity, metal ions concentrations, and low concentration of dissolved oxygen (DO5). In this study, we report the variations in selected physicochemical parameters of waters of the Rwabakazi river. Turbidity, pH, concentrations of selected metal ions, T.S.S., and DO5 of water sampled from three selected sites on the river in Kabale were very high. Mean DO5 fell from 96 ± 2 mg/L to 86± 1.5 mg/L downstream. The mean pH fell from 7.8 ± 0.03 to 7.6 ± 0.04, showing the removal of basic components. The turbidity dropped from370 ± 3 NTU to 305 ± 2 NTU, showing that the haziness of water decreased. The concentration of iron(II) fell from 320 ± 0.3 mg/L to 291 ± 0.2 mgL-1 indicating the fair extent of heavy metal ions downstream. The T.S.S. decreased from 330 ± 5 mg/L to 300± 5 mg/L, and concentrations of calcium and magnesium ions also decreased, providing evidence for self-purification. The available data suggests that river Rwabakazi is polluted as a result of poor agricultural practices, erosion, and flash flooding. Further studies on nutrient and pesticide pollution of this river need to be carried out, and trees should be planted on steep open surfaces to minimize erosion.